Elaboração, validação e implementação de um protocolo de gerenciamento do manejo da sepse em um hospital de alta complexidade - Junglos, Patrícia (2024)
In 2016, the Third International Consensus (Sepsis-3) was carried out, and the definition of sepsis as a life-threatening organ dysfunction due to a dysregulated host response to infection was published. Although sepsis is widely discussed in the scientific literature, there is still a great need to implement strategies that encourage continuing education regarding the sepsis management protocol in the emergency room and intensive care units of high-complexity hospitals.The general objective was to outline the epidemiological profile of patients admitted to the institution and to implement a protocol for managing sepsis management. To respond to the objectives, a cross-sectional research and methodological study were carried out. To carry out the cross-sectional study, data collection was carried out in medical records from January to December 2023 through a structured form, aiming to compile epidemiological data from adult patients admitted to the emergency room and intensive care units with a diagnosis of sepsis and to outline the profile with identification of the outcome of discharge and death.The methodological study took place in five stages: situational diagnosis, literature review, protocol construction, content validation, and protocol implementation. For the first stage, a survey was carried out with the care professionals about their previous knowledge related to sepsis and management protocol. In the second stage, for the literature review, a search was carried out on the LILACS, PubMed and Google Scholar platforms, in search of scientific articles and guidelines on the subject. In the construction of the protocol, the results of the first and second stages were used as support for the inclusion of the contents.After the construction of the content, the protocol was validated, where a specific questionnaire was applied to eligible professionals (judges) with care and specialization in the areas of Urgency and Emergency or Intensive Care or General Surgery, Infectious Diseases and Biomedicine. After validation, the implementation phase was carried out. In this phase, a video was prepared as a form of training, consisting of a compilation of the content of the protocol, which was applied to the on-call physicians of both the medical and nursing teams who work in the Emergency Room and Intensive Care Units.After the training, the professional answered another questionnaire that aimed to assess knowledge about sepsis and the form of treatment and management according to the protocol developed. The Research Ethics Committee authorized the research – COPEP, of the State University of Maringá, as recommended by Resolution 466/12 through opinion No. 6,014,607 and approved on April 21, 2023. Protocol No. CAAE 66526722.5.0000.0104. The results obtained showed that the outcome with death was higher in males, corresponding to 55.5% of the cases, and among the elderly, where death occurred in 71.9% of the cases. It was observed that the predominant focus was the pulmonary focus, followed by the urinary focus.After the elaboration of the protocol, the validation phase took place, where the CVI calculation was performed to verify the agreement of the "judges". All judges agreed with the proposed items and some suggested small changes and insertions, which were met and the protocol readjusted. During the training, the protocol was presented, with subsequent evaluation of the level of knowledge about sepsis, and it was found that most of the participating professionals have regular to good knowledge about sepsis, but in relation to the treatment and management of sepsis, most are outdated, especially in relation to the guidelines for immediate volume replacement; the use of vasopressors in patients with mean arterial pressure less than or equal to 75 mmHg and the reassessment of perfusion parameters after volume resuscitation.In view of the above, there is a need for educational actions that update such knowledge, aiming at the successful implementation of this sepsis management protocol, which can present positive results both for institutional management and for improving the care of patients with sepsis.